Kriteria Perancangan Kawasan Wisata Rekreatif Islami - Dara Wisdianti (Arsil Media, 2023)
The development of tourist areas is influenced by various factors, both in the form of physical factors related to the context of the area and non-physical factors related to community characteristics related to the cultural context. The coastal area of Ulee Lheue, Banda Aceh is a very potential area to be developed as a tourist area. In its development, it is necessary to consider its compatibility with Islamic Shari'a which is the prevailing culture in Acehnese society. The applicable Islamic Shari'a can be outlined in Islamic architectural design criteria. The results of the architectural design can be realized in the form of recreational tourism activities by Islamic Shari'a.